Look! : the fundamentals of art history - D'Alleva, Anne (Boston : Prentice Hall, 2010)
Introducing art history -- Formal analysis -- Contextual analysis -- Writing art - history papers -- Navigating art - history examinations -- Art history's own history -- Glossary.
Includes bibliographical references and index.
boek
Keywords: Art -- Study and teaching (Higher) -- Methodology; Art -- Historiography